(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Leprosy (Hansens disease) is one of the major health problems of the world especially in developing countries. In India, it was first described in Sushruta Samhita & treated by Chaulmoogra oil and caused by Mycobacterium Leprae. Early diagnosis of leprosy, an absolute necessity for control as well as effective therapy. For this, clinical diagnosis, skin smear examination is adequate coupled with histo-pathological examination of skin and nerve lesions with modified Fite Faraco stain for demonstration of acid-fast bacilli. Moreover, bacillary index is required for adequate combined chemotherapy regimen. Detection of anti PGL-1 antibodies in serum gives an added advantage for detection and monitoring treatment. Materials & Methods : A total of 85 cases of leprosy who attended outpatient department of Skin & VD, Shri Sayaji General Hospital Baroda chosen for study during 07-08 period with 75 cases from leprosy hospital, Baroda which included 50 detected patients and 25 child contacts with 25 healthy voluntary blood donors from blood bank, SSGH selected. Clinical, past and family history taken with slit skin smears stained with Z-N stain, graded and histopathological evaluation done. Serological study done from serum of leprosy patients and healthy blood donors; tested by Serodia Kitsand interpretation made. Results: Most cases were in 2nd to 4th decade and males dominated. Clinically most cases were of indeterminate and tuberculoid type and histologically indeterminate and border-line tuberculoid. Clinico-histopathological correlation was found most in indeterminate followed by histoid type. Voluntary blood donors were seronegative. 21 out of 48 multibacillary cases and 6 out of 28 pauci-bacillary showed seropositivity for anti PGL-1 anti-bodies (p<0.001) Conclusion: All suspected leprosy cases clinically should be subjected to slit skin smear examination with histopathological evaluation; bacillary study which helps in diagnosis and adequate treatment of patients. Detection of antibodies to PGL-1 in patients indicate presence of leprosy bacilli and useful in preclinical diagnosis and determining progress of therapy. DOI: http://dx.doi.org/10.3329/bjms.v13i3.9153 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.316-322